155 The impact of an integrated renal supportive care service on symptom burden, advanced care planning and place of death for patients with advanced chronic kidney disease managed without dialysis. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Douglas, CA; Sloan, JM; Witham, M; Cathcart, S; Stage, L; Frame, L; Lafferty, ME
Abstract : Background: We redesigned a Renal Supportive Care (RSC) service in 2012 for patients with chronic kidney disease (CKD) managed without dialysis. We audited the service to evaluate impact on symptoms and care pathways. Methods: The RSC service allows consultations over a wide geographical area and includes a RSC nurse, a Renal consultant and a Palliative Medicine consultant. The main focus is continuing care of CKD, symptom management and Advanced Care Planning. A retrospective case-note audit was performed from April 2012 until October 2014 on all known patients who had chosen non-dialytic management. Data collected included demographics, RSC input, Palliative Care Outcome Score (POS), anticipatory care plan (ACP) information and mortality data. Results: 98 patients were managed with non-dialytic care during the audit period. 72% (71/98) received RSC consultations. 72% (57/79) of patients who received a RSC consultation had a full assessment of symptoms using the POS with an improvement in total symptom burden from a median score of 11 to 8, between the first and last consultation (p=0.03). For patients with RSC input, 79% (56/71) had an ACP compared to 19% (5/27) without (p<0.001). Preferred Place of Care (PPC) was documented in 68% (48/71) and 26% (7/27) in each respective group (p<0.001). PPC was community in 100%. DNA CPR was documented in 84% (57/68) of patients with RSC input and 47% (8/17) without (p=0.001). During the audit, 62% (61/98) of patients died. 29% (11/38) of patients with an ACP died in an acute hospital versus 43% (10/23) of those without (p=0.25). 24% (8/34) of patients with documented PPC died in acute hospitals versus 48% (13/27) without documentation (p=0.04). Conclusions: The Renal Supportive Care team achieved symptom management and Advanced Care Planning for many patients with CKD managed without dialysis and may help achieve preferred place of care.